Doctor of Medical Science, Professor, Honoured Scientist of Ukraine Sukmansky Oleh Ivanovych (to his 90th birthday) - Khudiakov et al., O.E. (Medicni Perspektivi, 2021)
Doctor of Medical Science, Professor, Honoured Scientist of Ukraine Sukmansky Oleh Ivanovych (to his 90th birthday)